Knockdown of Hypoxia-Inducible Factor 1α Improved the Efficacy of Low-Dose Metronomic Chemotherapy of Paclitaxel in Human Colon Cancer Xenografts. (October 2017) - Zhang, Mu; Chen, Chen; Su, Feng; Huang, Zhiguo; Li, Xiangmin; Li, Xiaogang
Low-dose metronomic chemotherapy represents a new strategy for solid tumor treatments with a strong antiangiogenic activity and few side effects. However, low-dose metronomic therapy alone is not always as effective as traditional chemotherapy on eradication of tumor. On the contrary, low-dose metronomic in some cases could stimulate tumor growth due to hypoxia of tumor cells induced during therapy. Our study aimed to investigate whether knockdown of hypoxia-inducible factor-1α expression in tumor cell could facilitate low-dose metronomic therapy with paclitaxel for human colon cancer. Human colon cancer cell line (HT-29) stably transfected with specific short hairpin RNAs silencing hypoxia-inducible factor-1α exhibited marked attenuation of hypoxia-induced expression of the target genes such as vascular endothelial growth factor, glucose transporter 1, and P-glycoprotein. Compared with HT-29-c xenograft tumor model established by subcutaneous injection of HT-29 cells stably transfected with scrambled control short hairpin RNA, HT-29-ih xenograft tumor model showed more significant and long-lasting antitumor responses of empirical metronomic paclitaxel regimens, accompanied by drastic angiogenesis decrease and neglectable toxicity. All these data indicated that the combination of paclitaxel low-dose metronomic therapy with hypoxia-inducible factor-1α knockdown might provide a potent battle against colon cancer.